Ewing sarcoma of the pancreas: a pediatric case report and narrative literature review - Liu, Zhensheng; Bian, Jian; Yang, Yong; Wei, Decheng; Qi, Shiqin (Frontiers in Oncology, 2024)
Ewing's Sarcoma (ES) is an rare, small round-cell sarcoma that predominantly occurs in children and young adults, with both skeletal and extraskeletal manifestations. However, pancreatic ES, due to its rarity, is infrequently featured in scholarly literature, with only a scant 43 reported instances. Our study describes a case of pancreatic ES in an 8-year-old boy who was found to have an abdominal mass. Following an exhaustive examination, the boy was diagnosed with a neoplasm in the pancreatic head and underwent a complex surgical procedure encompassing pancreatoduodenectomy and partial transverse colectomy. Immunohistochemical assays confirmed the neoplastic cells' positivity for Cluster of Differentiation 99(CD99), Vimentin, and NK2 Homeobox 2(NKX2.2), while genomic testing identified an EWSR1-FLI1(Ewing Sarcoma Breakpoint Region 1–Friend Leukemia Integration 1) gene fusion. This led to a conclusive diagnosis of pancreatic Ewing's Sarcoma. The patient underwent seven cycles of adjuvant chemotherapy, alternating between VDC (Vincristine, Doxorubicin, Cyclophosphamide) and IE (Ifosfamide, Etoposide) tri-weekly, but did not undergo radiotherapy. At present, the patient remains neoplasm-free. Through our case analysis and comprehensive review of the existing literature, we aim to underscore th rarity of pancreatic Ewing's sarcoma and to highlight the efficacy of our individualized therapeutic approach.